To punish or repair? Evolutionary psychology and lay intuitions about modern criminal justice - Petersen, Michael Bang (2012)
We propose that intuitions about modern mass-level criminal justice emerge from evolved mechanisms designed to operate in ancestral small-scale societies. By hypothesis, individuals confronted with a crime compute two distinct psychological magnitudes: one that reflects the crime’s seriousness and another that reflects the criminal’s long-term value as an associate. These magnitudes are computed based on different sets of cues and are fed into motivational mechanisms regulating different aspects of sanctioning. The seriousness variable regulates how much to react (e.g., how severely we want to punish); the variable indexing the criminal’s association value regulates the more fundamental decision of how to react (i.e., whether we want to punish or repair). Using experimental designs embedded in surveys, we validate this theory across several types of crime and two countries. The evidence augments past research and suggests that the human mind contains dedicated psychological mechanisms for restoring social relationships following acts of exploitation.